Needs affordance as a key factor in likelihood of problematic social media use: Validation, latent Profile analysis and comparison of TikTok and Facebook problematic use measures. (June 2022) - Smith, Troy; Short, Andy
Highlights: The problematic Facebook and TikTok scales have appropriate psychometric properties in the Caribbean cultural context. The optimal cut-off score of the Problematic TikTok Use Scale was determined to be 21. The criteria with the highest predictive power in the diagnosis of problematic TikTok use are "withdrawal" and "relapse". Loneliness is positively associated with both problematic TikTok and Facebook use. Self-esteem is negatively associated with problematic Facebook use only. Abstract: Despite increasing concerns of maladaptive cognitive responses associated with social media, estimates of its prevalence are lacking in the literature. Further, existing studies have disproportionately focused on Facebook, while ignoring the penetration of TikTok and concerns of associated maladaptive behaviors. This study aims to 1) validate scale measures for problematic Facebook and TikTok use (PFU and PTTU) 2) comparatively assess the underlying cognitive pathways of the PFU and PTTU among a sample of university students, 3) determine the cut-off score of the PTTU assessment scale using Latent Profile Analysis (LPA) and 4) evaluate the contribution of specific criteria in the diagnosis of PTTU. The scales used to assess PFU and PTTU were found to have appropriate psychometric properties. The scores between the PFU and PTTU scales were found to be strongly associated, however, the relationship was stronger in the group of Facebook users than in the group of TikTok users. Further, the manifestation of problematic use was not consistent between TikTok and Facebook. Loneliness was positively associated with both PFU and PTTU, while self-esteem was negatively associated with PFU only. The optimal cut-off score of the PTTU scale was determined to be 21, giving 8.7% as the estimated prevalence of PTTU. The criteria with the highest predictive power in the diagnosis of addiction among university students were "withdrawal" and "relapse". The study concludes that while the underlying addiction pathways are similar between platforms the manifestation of maladaptive behavior and the drivers for usage intensity and problematic use are unique.